DNA extraction and electrophoretic visualization for genetic study of gerga and calamansi citrus varieties - Amida, Nadia; Maria Titin Supriyanti, Florentina (Arfak Chem: Chemistry Education Journal, 2025)
This study aimed to isolate and characterize the genomic DNA of Gerga orange (Citrus gerga) and Calamansi (Citrus microcarpa) using the Cetyl Trimethyl Ammonium Bromide (CTAB) method, followed by agarose gel electrophoresis analysis. The research serves as an initial step toward understanding the genetic relationships among local citrus varieties from Bengkulu, Indonesia. Young leaves were selected as DNA sources due to their metabolically active tissues and relatively low concentrations of secondary metabolites that can inhibit DNA extraction. The isolation procedure included tissue maceration, cell lysis, removal of proteins and polysaccharides, and precipitation of purified DNA. Electrophoresis using a 1 kb DNA ladder revealed distinct genomic DNA bands larger than 10,000 base pairs (bp) in both Gerga (G3) and Calamansi (K3) samples, indicating successful extraction of high-molecular-weight DNA. Subsequent PCR electrophoresis showed approximately 500 bp amplified fragments in the Gerga (G5) and Calamansi (K3) samples, as indicated by the 1 kb DNA ladder. These findings confirm that the CTAB method yields high-quality, intact DNA suitable for further molecular investigations, including genetic identification, phylogenetic reconstruction, and the study of genetic diversity among Bengkulu’s local citrus species.